1984
DOI: 10.48044/jauf.1984.057
|View full text |Cite
|
Sign up to set email alerts
|

Insecticides For Control of Bark Beetles That Spread Dutch Elm Disease

Abstract: Chlorpyrifos, carbaryl and methoxychlor were compared for the following uses against elm bark beetles: 1, elimination of broods in infested elm wood; 2, exclusion of colonization of uninfested elm logs; 3, toxicity to beetles "landing" on treated elm bark; 4, prophylaxis against twig feeding. Chlorpyrifos killed virtually 100% of the beetle broods, completely excluded colonization of uninfested logs and was toxic to 90% or more of the beetles exposed for 10 seconds to bark sprayed 6 weeks earlier. Methoxychlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Mortality inflicted on the extant generation of European elm bark beetles can be maximized by baiting the tree with the pheromone Multilure (DeWill Inc., Elmhurst, IL) (21) and treating the lower bole (4-5 cm) with an insecticide. In tests of several insecticides for this purpose, chlorpyrifos (Dursban, Dow Chemical Co., Wilmington, DE) emerged as the compound of choice; a 10-sec exposure on bark sprayed with 0.5% chlorpyrifos killed 90% or more of the European and native elm bark beetles six weeks after treatment, while 1 -min exposures were lethal to nearly 100% of the beetles throughout the 10-week experiment (14). Recent work (20) found that several pyrethroid insecticides (Esfenvalerate (ASANA), DuPont; cypermethrin (AMMO) and permethrin (POUNCE), both FMC Inc. and Fluvalinate (MAVRIK Aquaflow), Sandoz Crop Protection) could also be very effective for this treatment.…”
mentioning
confidence: 99%
“…Mortality inflicted on the extant generation of European elm bark beetles can be maximized by baiting the tree with the pheromone Multilure (DeWill Inc., Elmhurst, IL) (21) and treating the lower bole (4-5 cm) with an insecticide. In tests of several insecticides for this purpose, chlorpyrifos (Dursban, Dow Chemical Co., Wilmington, DE) emerged as the compound of choice; a 10-sec exposure on bark sprayed with 0.5% chlorpyrifos killed 90% or more of the European and native elm bark beetles six weeks after treatment, while 1 -min exposures were lethal to nearly 100% of the beetles throughout the 10-week experiment (14). Recent work (20) found that several pyrethroid insecticides (Esfenvalerate (ASANA), DuPont; cypermethrin (AMMO) and permethrin (POUNCE), both FMC Inc. and Fluvalinate (MAVRIK Aquaflow), Sandoz Crop Protection) could also be very effective for this treatment.…”
mentioning
confidence: 99%